A highly durable catalyst system for hydrogen production from dimethyl ether - Stöber, Robert; Seidl, Franziska; Hoffmann, Emanuel; Wasserscheid, Peter; Schühle, Patrick (Sustainable Energy & Fuels, 2024)
Dimethyl ether (DME) is a promising vector for the transportation of hydrogen over long distances and from point to point. However, a major challenge to the large-scale application of this technology has been the notoriously unstable nature of the so far applied steam reforming catalysts. In this paper, we describe a physical mixture of γ-Al2O3 and zirconia-supported In2O3 as a highly stable catalyst system for the steam reforming of dimethyl ether (SRD). Our work shows that the use of 3 wt% In2O3 on ZrO2 provides the highest activity and hydrogen yield in the temperature range of 350-400 °C. In addition, the developed catalyst system shows excellent stability over an operating time of 425 h with a DME conversion of nearly 100% and a hydrogen yield of about 90%. To maximize the hydrogen yield further, a water-gas shift reactor was operated downstream of the SRD reactor, but at lower temperatures, to reduce the CO concentration in the product mixture to its thermodynamic equilibrium concentration. This synergetic operation led to a maximum hydrogen yield of 95%.
CRIS-Team Scopus Importer:2024-05-03